THE GUIDES FOR TEACHING PARTS OF THE SPEECH - Safiya Solihova Azamatovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Undoubtedly, it is important for each learner to master and differentiate parts of speech correctly. The parts of the speech are the fundamental categories of words based on their grammatical function including with meaning within a sentence. Understanding and being able to teach parts of speech correctly are essential for comprehending sentence structure.Teachers ought to know how to teach them since without knowing the parts of speech properly, students will not be able to make sentences correctly. This article will provide the most effective strategies for teaching parts of speech to students of various ages and abilities.